1972
DOI: 10.4141/cjps72-165
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Data on the Rate of Photosynthesis, Respiration, and Transpiration of Different Organs in Awned and Awnless Isogenic Lines of Wheat

Abstract: Net photosynthesis, respiration, and transpi-for the awnless and awn-clipped heads than ration were determined on heads and flag for the awned head. Respiration rates of the leaves of two isogenic lines of wheat (Tri-heads were L.7 and 3.0 times greater than ticum aestivum Ll em Thell) by measdring the respiration rates of the flag leaves of the the difference in CO, and water-vapor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
10
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 3 publications
2
10
0
Order By: Relevance
“…Awns contributed substantially to the fixation of carbon-14 dioxide by the canopy (Table 4) and increased fixation by the entire ears by an average of 7'9% in the tall and I 1-6 % in the dwarf genotype. This result is in accordance with those from several other studies in which ear photosynthesis, assessed by infra-red gas analysis, has been shown to be considerably increased by the presence of awns (Apel, 1966;Evans & Rawson, 1970;Teare et al 1972;Olugbemi et al 1976). In our study, the awns alone S.E.…”
Section: Discussionsupporting
confidence: 94%
“…Awns contributed substantially to the fixation of carbon-14 dioxide by the canopy (Table 4) and increased fixation by the entire ears by an average of 7'9% in the tall and I 1-6 % in the dwarf genotype. This result is in accordance with those from several other studies in which ear photosynthesis, assessed by infra-red gas analysis, has been shown to be considerably increased by the presence of awns (Apel, 1966;Evans & Rawson, 1970;Teare et al 1972;Olugbemi et al 1976). In our study, the awns alone S.E.…”
Section: Discussionsupporting
confidence: 94%
“…farther south (Schaller et al 1972 These results and those of Qualset et al (1965) and Teare et al (1972) Data from the present test and those reported by Schaller et aL. (1972) suggest that long awns are of greatest advantage for yield where there is not a moisture stress.…”
Section: Results Yearssupporting
confidence: 80%
“…The importance of the lemma awn as a comparison of isogenic lines differing only photosynthetic structure in cereals, particu-in the alleles affecting awn length plus their larly barley (Hordeum vulgare L.) and wheat associated linkage blocks (Evans et al 1972; (Triticum aestivum L.), is widely accepted Jagathesan et al 1961;Patterson et al19621' because studies using diverse methods have Qualset 1968;Qualset et al 1965;Schaller indicated that awn length is positively related Suneson et al 1948;Teare et al to seed size and yield (Grundbacher 1963; "Full-", "Half-", "Quarter-1962;Qualset 1968;Qualset et at. 1965;awned" and "Awnless" phenotypes (Qualset Saghir et al 1968;Schaller et al 1972;1968;Qualset et al 1965;Schaller et al Suneson et al 1948;Teare et al 1972;Yer-1972).In a series of yield tests conducted in velde 1953; Walpole and Morgan 1972).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat awns windrower-combine harvest system used contain stomata (Teare et al 1972a) which in Canada, since awns would help to hold carry on gas exchange (Teare et al 1972b Pool and Patterson (1958) found that an ins wheat. awned soft red winter wheat cultivar lost 0008-4220 I 821 620 1-000 1 $2.00 …”
mentioning
confidence: 99%